Geographic and temporal patterns of variation in total mercury concentrations in blood of harlequin ducks and blue mussels from Alaska. Issue 1 (15th April 2017) - Savoy, Lucas; Flint, Paul; Zwiefelhofer, Denny; Brant, Heather; Perkins, Christopher; Taylor, Robert; Lane, Oksana; Hall, Jeff; Evers, David; Schamber, Jason
Abstract: We compared total mercury (Hg) concentrations in whole blood of harlequin ducks ( Histrionicus histrionicus ) sampled within and among two geographically distinct locations and across three years in southwest Alaska. Blue mussels were collected to assess correlation between Hg concentrations in locally available forage and birds. Mercury concentrations in harlequin duck blood were significantly higher at Unalaska Island (0.31 ± 0.19 mean ± SD, μg/g blood) than Kodiak Island (0.04 ± 0.02 mean ± SD, μg/g blood). We found no evidence for annual variation in blood Hg concentration between years at Unalaska Island. However, blood Hg concentration did vary among specific sampling locations (i.e., bays) at Unalaska Island. Findings from this study demonstrate harlequin ducks are exposed to environmental sources of Hg, and whole blood Hg concentrations are associated with their local food source. Highlights: Harlequin ducks accumulate environmental sources of mercury. Mercury concentrations in harlequin duck whole blood is associated with mercury concentrations in blue mussels. Mercury accumulation by harlequin ducks varies geographically. Mercury accumulation in harlequin ducks did not vary annually. Mercury accumulation in harlequin ducks was not influenced by their age class or gender.